Synthetic adhesive oligopeptides with rigid polyhydroxylated amino acids1. Issue 5 (20th February 2013) - Deshmukh, Manjeet; Singh, Shashi; Geyer, Armin
Abstract Synthetic oligopeptides containing polyhydroxylated bicyclic dipeptide (GlcTap) are investigated for their adhesion properties. The non‐natural amino acid building block composed of GlcTap is derived from glucuronic acid and mimics the hydroxyl‐amino acids of the natural proteins. Peptide oligomers of GlcTap flanked by the amino acids Tyr and Lys were synthesized and characterized. Solution structural studies performed by circular dichromism spectroscopy suggests that poly(LysGlcTapTyr) and poly(GlcTapTyr) adopts extended helical structures. Adhesion of these oligomers to the mica surface is shown by atomic force microscopy spectroscopy. Studies indicate that extended polyproline II polyhydroxylated peptide chains, which bear additional phenolic as well as cationic side chains, can mimic some of the adhesion properties of the natural protein models. Furthermore, obtained data suggest that poly(GlcTapTyr) and poly(LysGlcTapTyr) as outstanding adhesive compounds, which combine efficient synthetic accessibility with promising adhesive properties. © 2012 Wiley Periodicals, Inc. Biopolymers 99: 273–281, 2013.